A Novel Antimicrobial Coating Represses Biofilm and Virulence-Related Genes in Methicillin-Resistant Staphylococcus aureus - Vaishampayan, Ankita; de Jong, Anne; Wight, Darren J.; Kok, Jan; Grohmann, Elisabeth (Frontiers in Microbiology, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) has become an important cause of hospital-acquired infections worldwide. It is one of the most threatening pathogens due to its multi-drug resistance and strong biofilm-forming capacity. Thus, there is an urgent need for novel alternative strategies to combat bacterial infections. Recently, we demonstrated that a novel antimicrobial surface coating, AGXX®, consisting of micro-galvanic elements of the two noble metals, silver and ruthenium, surface-conditioned with ascorbic acid, efficiently inhibits MRSA growth. In this study, we demonstrated that the antimicrobial coating caused a significant reduction in biofilm formation (46%) of the clinical MRSA isolate, S. aureus 04-02981. To understand the molecular mechanism of the antimicrobial coating, we exposed S. aureus 04-02981 for different time-periods to the coating and investigated its molecular response via next-generation RNA-sequencing. A conventional antimicrobial silver coating served as a control. RNA-sequencing demonstrated down-regulation of many biofilm-associated genes and of genes related to virulence of S. aureus. The antimicrobial substance also down-regulated the two-component quorum-sensing system agr suggesting that it might interfere with quorum-sensing while diminishing biofilm formation in S. aureus 04-02981.